A impossibilidade da interdisciplinaridade: apontamentos para alternativas socioconstrutivistas - Léo Peixoto Rodrigues (Ciências Sociais Unisinos)
This article aims to provide a reflection, from a point of view of social sciences, on the theoretical and empirical scientific practices, commonly referred to as interdisciplinary. We pointed out that interdisciplinarity is almost impossible, due to the current theoretical model that organizes Science. We present three significant obstacles to effective interdisciplinary knowledge practices. These are: epistemological obstacle, political and institutional obstacles and complexity. After problematizing, the proposed obstacles, we proposed possibilities to a renewed constructivist reflection to the interdisciplinarity scientific practice, which we call “onto-epistemological”. We emphasize that it is important to rethink the theoretical aspects of the organization of knowledge itself.